2023
DOI: 10.1002/eji.202350574
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells reduce neuroretina inflammation in mouse by regulating autoreactive Th1 and Th17 cells through IFN‐γ

Sihan Wu,
Xuan Zhang,
Cuiping Hu
et al.

Abstract: Various regulatory CD8+ T cell subsets have been proposed for immune tolerance and have been implicated in controlling autoimmune diseases. However, their phenotypic identities and suppression mechanisms are not yet understood. This study found that coculture of T cell receptor (TCR)‐ or Interferon (IFN)‐β‐activated CD8+ T cells significantly suppressed the cytokine production of Th1 and Th17 cells. By experimenting with the experimental autoimmune uveitis (EAU), we found that adoptive transfer of TCR or IFN‐β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In another study, Gunderson et al found that CD8 + T cells induced psoriatic-like skin inflammation through IFN-γmediated pathways (Gunderson et al, 2013). Conversely, Wu et al observed that CD8 T cells could regulate autoreactive Th1 and Th17 cells via IFN-γ, thereby reducing neuroretinal inflammation in mice (Wu et al, 2023). Hence, we speculate that the role of CD8 in modulating the inflammatory response may be dual, with outcomes influenced by factors such as the disease site or type, animal model, or target population.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Gunderson et al found that CD8 + T cells induced psoriatic-like skin inflammation through IFN-γmediated pathways (Gunderson et al, 2013). Conversely, Wu et al observed that CD8 T cells could regulate autoreactive Th1 and Th17 cells via IFN-γ, thereby reducing neuroretinal inflammation in mice (Wu et al, 2023). Hence, we speculate that the role of CD8 in modulating the inflammatory response may be dual, with outcomes influenced by factors such as the disease site or type, animal model, or target population.…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells are implicated in the pathogenesis of various autoimmune diseases, and pathogenic Th17 cells are thought to induce immune cell infiltration and tissue damage by secreting pro-inflammatory cytokines, including IL-17A, IL-17F, IL-22, and granulocyte-macrophage colony-stimulating factor. Numerous studies using experimental autoimmune uveitis animal models have demonstrated that retinal antigen specific Th1 and Th17 cells can induce autoimmune uveitis in naive mice through adoptive transfer [5,8] . In this study, compared to the non-uveitis group, the proportions of Th1 and Th17 cells in uveitis patients were significantly elevated before treatment.…”
mentioning
confidence: 99%
“…In another study, Gunderson et al found that CD8 + T cells induced psoriatic-like skin inflammation through IFN-γmediated pathways (Gunderson et al, 2013). Conversely, Wu et al observed that CD8 T cells could regulate autoreactive Th1 and Th17 cells via IFN-γ, thereby reducing neuroretinal inflammation in mice (Wu et al, 2023). Hence, we speculate that the role of CD8 in modulating the inflammatory response may be dual, with outcomes influenced by factors such as the disease site or type, animal model, or target population.…”
Section: Discussionmentioning
confidence: 99%